TEACHER TEAMS AND SCHOOLS BECOME LEADERS TO DISSEMINATE INNOVATIVE PRACTICE - Namsone, Dace; Čakāne, Līga; Sarceviča - Kalviške, Dina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
We will introduce a study about teachers taking part in networking for personal development and becoming teacher leaders. In 2011 a multilevel national joint collaboration network of schools with innovative experience was created to foster dissemination of new teaching and learning experiences among teachers. In order to organize learning for teachers, a lesson based collaborative continuous teacher professional learning model was implemented. The research shows that conducting and analyzing lessons has helped participants become more competent professionals and develop skills that are crucial for a good leader. Categories characterizing teacher leaders and lead schools were identified. Factors that facilitate or limit teachers or schools to become leaders are discussed.